Perancangan Automatic Sprinkler System Pada Gudang Batu Bara Perusahaan Produksi Susu - Hasna Hayba Silmiy; Annastasya Aulia Putri; Muhammad Alfiyan Fikri; Moch. Luqman Ashari (JURNAL ILMIAH TEKNIK INDUSTRI DAN INOVASI, 2023)
Fire is a condition that occurs due to the oxidation of three elements (fuel, oxygen and heat) which can cause property losses, injury to death. One of the places that is prone to fire is a coal storage warehouse, considering the characteristics of the materials stored in it. In order to reduce losses due to fires, an automatic sprinkler system is needed in the coal warehouse of a dairy production company to help extinguish the fire as soon as possible when a fire occurs. Based on these problems, this research will determine the number of sprinklers needed as an automatic extinguishing system as well as the volume of water, pump power, and groundwater tanks. This type of research is quantitative research by direct observation of the object under study, then the researcher measures the coal warehouse space using a building meter. From the results of calculations by taking a sample of the coal warehouse room of a dairy production company, the required number of sprinklers is 111, the required water volume is 399.6 ????3, the required pump power and ground water tank are, pump hydraulic power (HHP) 1.2910128 kW, pump shaft power (BHP) 1.7213504 kW, pump electric power (P) 3 kW, diesel pump (PpD) 2 HP, jocky pump (PJk) 0.3 kW, GWT capacity (QGWT) 17 m3.